Making a Non-White America : Californians Coloring outside Ethnic Lines, 1925-1955. - Varzally, Allison (University Presses of California, Columbia and Princeton, 2004)
Looks at eclectic neighborhoods in California where multiple minorities constituted the majority during formative years of the twentieth century. This study examines everyday interactions among the Asian, Mexican, African, Native, and Jewish Americans, and others who lived side by side.